Pengaruh Return On Equity (ROE), Gross Profit Margin (GPM) Dan Pertumbuhan Penjualan Terhadap Harga Saham Pt.Indofood Cbp Sukses Makmur Tbk - anti, yuli; Huda, Nurul (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This study aims to analyze how much influence roe, gpm, and sales growth have on prices. the sampling method used purposive sampling, with these criteria obtained a sample of 10 years. the type of data used in this study is secondary data which is processed using the SPSS version 22 application. The results show that the variables roe, gpm, and sales growth simultaneously have the same effect on stock prices, and partially show only gpm variables that affect stock prices , while the coefficient of determination (R2) the independent variable can explain its effect with a potential of 71.7% and the remaining 28.3% is explained by other variables.